THE EFFECT OF PATIENCE ON ACADEMIC HARDINESS IN OVERSEAS STUDENTS AT THE FACULTY OF PSYCHOLOGY, UNIVERSITAS ISLAM RIAU - Annisa Putri; Ahmad Hidayat, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The phenomenon of going abroad for education can bring various difficulties in fulfilling a student's major task, specifically studying. So it requires academic hardiness to be able to survive the academic pressure. One of the factors that formed academic hardiness is patience. This research aims to analyze the effect of patience on academic hardiness in overseas students at the Faculty of Psychology, Universitas Islam Riau . The subjects in the research were 115 overseas students and the sampling technique used is purposive sampling technique. This research uses 3-FPQ scale to collect the data, with 11 items and the RAHS scale consists of 40 items. The data analysis method used in this research is Partial Least Square (PLS) with smartPLS 3.0 software. The result gained in this research is that patience has a positive and significant effect on academic hardiness with 0.333 of path coefficient value, 0.001 <0.05 of p value and 3.210 of t value. It shows that the increase of patience can increase the academic hardiness in overseas students at the Faculty of Psychology, Universitas Islam Riau. Recommendations for further research are expected to examine other factors that may have a greater impact on academic hardiness and further expand the subject of research.